A systematic review of the Ayurvedic medicinal herb Bacopa monnieri in child and adolescent populations. (December 2016) - Kean, James D.; Downey, Luke A.; Stough, Con
Highlights: Bacopa monnieri significantly improved memory span as well as verbal and visual memory in children and adolescents. Two studies reported improvements in hyperactivity and attention in children diagnosed with ADHD. Significant outcomes demonstrated small to medium effect sizes (mean d = 0.42). Bacopa monnieri was well tolerated with only 2.3% of all participants reporting mild side-effects. Standardized trial designs in clinical paediatric populations are essential to ensure the outcomes reported are reliable and valid. Abstract: Objectives: Clinicians utilise critical research to advance their knowledge when prescribing standard and alternative therapies for developmental disorders. Recent research has reported that the traditional Ayurvedic medicine Bacopa monnieri may improve cognitive outcomes in adult populations; however, few studies have investigated its benefits in younger cohorts. The aim of the current review is to systematically assess and critically summarize clinical trial outcomes and safety of Bacopa and its effects on the cognition and behaviour in children and adolescents. Method: PubMed, Scopus, Cochrane Library, Google and CINAHL were searched up to August 2015 for trials investigating Bacopa monnieri in child and adolescent populations. There were no restrictions in study design. Cognitive and behavioural outcomes were grouped into validated constructs and effect sizes were calculated for all significant data to allow for direct comparisons. Results: Five studies met inclusion criteria for this review. The results demonstrated significant consistent improvements in the language behaviour cognitive domain and in a number of the memory sub-domains. Significant improvements were also seen in hyperactivity and attention-deficit domains. Overall outcome data demonstrated small to medium effect sizes (mean d = 0.42). Safety and tolerability data was well reported for 80% of studies with only 2.3% of all participants reporting mild side-effects. Conclusion: This review highlights the safe use of Bacopa monnieri in child and adolescent populations for improving elements of cognition as well as behaviour and attention-deficit domains. However, there is a significant need for replicated study designs and stringent statistical analysis to validate these outcomes.